PENGARUH PENGGUNAAN MEDIA FLASH CARD TERHADAP KETERAMPILAN MENULIS KARANGAN NARASI SISWA KELAS III SDN 188 PEKANBARU - Lydia Emilsa; Guslinda (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2019)
This research was motivated by the low level of students’ narrative essay writing skills. Several factors contributed to this condition, including students’ low interest and boredom in writing activities, limited vocabulary mastery, difficulties in word choice and spelling, and inadequate use of punctuation. As a result, students’ essays tended to be very simple, generally consisting of only one to two sentences, and lacked coherence between sentences, which prevented the formation of well-structured paragraphs. Students also experienced confusion in using punctuation marks such as periods, commas, question marks, and exclamation points correctly. This study aimed to determine the effect of using flash card media on the narrative essay writing skills of third-grade students at SDN 188 Pekanbaru. The research employed a quasi-experimental method using a nonequivalent control group design. The population of this study consisted of third-grade students at SDN 188 Pekanbaru, with Class IIIA (40 students) as the control group and Class IIIB (40 students) as the experimental group. The sampling technique used was saturated sampling. The research instrument was an essay test in the form of a narrative writing assignment. Hypothesis testing was conducted using the t-test and Effect Size (ES) analysis. The results showed that the use of flash card media had a significant effect on students’ narrative writing skills, with the magnitude of the effect categorized as medium.